OPTIMIZATION OF LOGISTICS ARRANGEMENT OF AVIATION INFRASTRUCTURE IN PAPUA - Dimas Endrawan; Musri Kona; Andi Batari Toja (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
The Air Bridge cargo air transport subsidy program in Papua aims to reduce price disparities and ensure logistics availability in the 3TP (Underdeveloped, Remote, Outermost, Border) regions that are highly dependent on air transportation. This study analyzes logistics movements and examines their implications for the capacity of airport cargo terminal infrastructure. The method used is descriptive with quantitative and qualitative approaches. This study integrates Least Square forecasting , Systematic Layout Planning (SLP) through Activity Relationship Chart (ARC), and safety and operational standards analysis. The analysis results project Sentani Airport's cargo load to reach 120,167 tons in 2026, which could trigger overcapacity conditions . Existing findings indicate weaknesses in warehouse layout and stockpiling that obstruct circulation routes. Optimization is focused on rearranging the layout through the ARC approach and separating specific goods placement using Systematic Layout Planning (SLP), as well as implementing strict Standard Operating Procedures (SOPs) for special cargo and perishable goods . This development, combined with the Business Model Canvas (BMC) strategy and optimal distribution routes, is essential to support an effective aviation logistics ecosystem in Papua.